Management and growth paradox of rural small-scale industrial sector in Ghana (Journal of Science and Technology, 2016)
It has been argued that Small Scale Industries (SSIs) scarcely grow rather they stagnate and most of them eventually die off mainly due to poor management. The situation has been blamed on a number of factors and therefore a systematic analysis of the key influential factors will givebetter understanding of the phenomenon. Data was mainly collected through interviews of owners/ managers of small industrial units in the Mfantseman District of Central Region of Ghana. Logistic regression was used to distinguish the factors influencing management and growth of the RSSI sector and to estimate the impact of each explanatory variable in the equations. The study shows that record keeping and banking, which are key ingredients of good management practices are largely influenced by the age of the firm, the type of technology used, how proprietors acquired their skills, the production level and the source of investment capital. Similarly, growth of firm is influenced by the gender of the proprietor, the sources of raw materials and how proprietors acquired their skill.